Association of Central Obesity and Salty Food Consumption with Small Dense LDL-C in Middle-Aged Indonesian Adults - Rohmaeni, Yeni; Hardinsyah, Hardinsyah; Tanziha, Ikeu (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2023)
This study aimed to investigate the association between central obesity and salty food consumption with the elevated of Small Dense Low-Density Lipoprotein-Cholesterol (sdLDL-C) among middle-aged Indonesian adults. Dietary behavior, together with the presence of obesity, leads to an increase in sdLDL-C. The study selected 8,611 subjects aged 49–64 years, from secondary data of a population-based survey conducted by the Ministry of Health of the Republic of Indonesia. The sdLDL-C concentration was determined using the Sampson equation. A significant association was observed between salty food consumption (OR=1.20; 95% CI: 1.04–1.38), general obesity (OR=2.59; 95% CI: 2.23–30), central obesity (OR=2.39; 95% CI: 2.11–2.70) and sdLDL-C. Diabetes and hypertension were positively associated with sdLDL-C, whereas Physical Activity (PA) was negatively associated with sdLDL-C. This study showed that obesity and consumption of salty food is associated with the increase of sdLDL-C, whereas PA is associated with the decrease of sdLDL-C.